The Protective Effects of Citrus Aurantium Extract on a 6-Hydroxydopamine-Induced Model of Parkinson's Disease in Male Rats - Leila Elyasi; Hamed Ghazvini (Negah Institute for Scientific Communication, 2020)
Introduction: Parkinson's Disease (PD) is a prevalent neurodegenerative condition among the elderly. Considering the limited symptomatic improvement associated with PD treatments, introducing more effective agents is necessary. Citrus aurantium flower extract (CAE) is recognized as a neuroprotective and hepatoprotective agent with bioactive compounds, such as flavonoids, phenolics, and vitamins. Considering the mitigating role of CAE against oxidative damage, the present study examined the neuroprotective effects of CAE in a PD model. Methods: Overall, 60 male rats were classified into 6 groups, as follows: sham (SH); control (C); lesion (L); and CAE-treated lesion (200, 400, and 600 mg/mL CAE+L). For the hemi-PD model, 6-hydroxydopamine (12.5 g/L of saline ascorbate) was injected intrastriatally. Intraperitoneal pretreatment with hydroalcoholic CAE (200, 400, and 600 mg/kg) was applied in the E+SH and E+L groups at one week pre-surgery. At two weeks post-surgery, rotational behaviors were examined by apomorphine hydrochloride. Moreover, stained neurons were measured in the Substantia Nigra pars compacta (SNc). Results: In comparison with the C group, significant contralateral turning was reported due to apomorphine, in the L group at two weeks post-surgery (P<0.0001); while the neuron count reduced on the left SNc (P<0.05). The rotational behaviors reduced using alcoholic CAE, and reduction in the neuron count of SNc was attenuated in the lesion groups (P<0.05). However, in the SH group, CAE caused no significant effects on apomorphine-induced rotation and neuron count in the SNc. CAE could decrease the number of degenerated neurons in the SNc. Cell count assessment revealed that neural cell count significantly increased in 200, 400, and 600 mg/mL CAE groups. Conclusion: According to the present findings, CAE can be suitable for preventing PD in rats.